Breastfeeding Self Efficacy and Perceived Stress in Primiparous Mothers - Farideh Bastani; Leili Rahmatnejad; Fereshteh Jahdi; Hamid Haghani (Iran University of Medical Sciences, 2008)
Background and Aim: Breastfeeding is a health-promoting and disease-preventing activity of mother with acceptable cost-effectiveness. Successful breastfeeding depends on various physiological and psychological factors such as maternal breastfeeding self efficacy and perceived stress. The aim of this study is to determine exclusive breastfeeding self efficacy and perceived stress in primipara mothers.   Materials and Methods: The data collection instrument was a questionnaire consisted of the demographic characteristics items, and breastfeeding self efficacy and perceived stress scales. Three hundred and thirty one primiparous women, referred to Shahid Akbarabadi Hospital in Tehran, were selected continuously (within three months) to complete the questionnaire.   Results: The results of this study showed that less than half of the subjects (46.5%) had high perceived stress level. In addition, more than 51.1% of mothers had high breastfeeding self efficacy. Therefore, according to the study findings and recent reports regarding reduced rate of breast feeding in Iran, it is necessary for health care responsible to provide appropriate strategies in order to increase breastfeeding self efficacy and stress management, especially in less experienced primipara women.   Conclusion: Accoding to findings and with due attention to recent decrease in breast-feeding in Iran, it is necessary to develop proper strategies in order to improving breast feeding self efficacy and effective stress management, especially in primiparous mothers.